Gender differences in the associations of recreational walking with indoor and outdoor falls among older adults-the Healthy Aging and Neighborhood Study (HANS) - Lingming Chen; Elizabeth Procter-Gray; Qun Le; Danielle LoPilato; Marianella Ferretto; Kevin Kane; Marian T. Hannan; Sarah Berry; Wenjun Li (AIMS Public Health)
ObjectiveThis study examined gender differences in the association between recreational walking and indoor and outdoor fall rates among older adults.MethodsThe Healthy Aging and Neighborhood Study is a prospective cohort that included 716 community-dwelling adults aged 65–95 years in central and northeastern Massachusetts, USA (2018–2023). Recreational walking at baseline was measured by the frequency of walking for exercise for at least 10 min in the participants' neighborhood. Falls were reported on monthly falls calendars, and the circumstances for reported falls were collected via subsequent telephone interviews. Mixed effects negative binomial models were used to estimate gender differences in the associations of recreational walking with rates of indoor and outdoor falls, separately. Models were adjusted for sociodemographic variables, physical health, functional status, lifestyle behaviors, mental health, and fear of falling.ResultsThere were 394 (55%) female and 322 (45%) male participants enrolled in the study, and the mean (SD) age was 74.08 (6.29). About 61% of participants engaged in recreational walking at least once weekly. Women had lower outdoor fall rates than men (32 vs. 40 per 100 person-years), while indoor fall rates did not significantly differ by gender (31 vs. 34 per 100 person-years). Women engaging in recreational walking at least once weekly had a 62% lower indoor fall rate [IRR (95% CI): 0.38 (0.21, 0.71)] than those who did not. No significant associations were observed between recreational walking and outdoor falls for both women and men.DiscussionAmong community-dwelling older women, but not men, a higher frequency of recreational walking was associated with lower rates of indoor falls, while no changes were seen with outdoor falls. Increasing recreational walking may be a viable focus for fall prevention programs in the community, especially for older women.